Towards a tokenization of carbon credits : an application of blockchain technology to emission trading system - Allanic, Maureen (My University, 2019)
Across the world, climate change is today one of the most major challenges of our time. Against it, several initiatives have been developed. One of them has the goal to cope with polluting emissions released into the atmosphere : The Emission Trading System. However, its success is threatened by several difficulties: frauds, lack of transparency, absence of standards and so on. All of these factors restrain Emissions Trading Systems to efficiently reduce global carbon footprint. This study investigates the potential of blockchain technology features applied the infrastructure of an emission trading system. In this perspective, this master thesis intends to demonstrate how blockchain can favor Emission Trading System mechanisms and prevent fraud issues from occurring. Analysis through surveys and semi structured interviews among experienced professionals have been realized in order to demonstrate and evaluate the feasibility of the designed system.
Keywords: Blockchain, Emissions Trading System, Climate Change